Evaluation of calculating carboplatin dosage in carboplatin–pemetrexed therapy as the first‐line therapy for Chinese patients with advanced lung adenocarcinoma. Issue 3 (29th January 2018) - Zhu, Yixiang; Xing, Puyuan; Wang, Shouzheng; Ma, Di; Mu, Yuxin; Li, Xue; Xu, Ziyi; Li, Junling
Abstract : Objective: This study aims to explore the application of actual carboplatin in carboplatin plus pemetrexed regimen as first‐line treatment for advanced lung adenocarcinoma, and to determine the recommended dose of carboplatin for Chinese populations. Methods: From January 2014 to April 2016, 151 advanced lung adenocarcinoma patients who received carboplatin and pemetrexed (500 mg/m 2 ) were included. The area under the curve (AUC) of carboplatin was back‐calculated from actual dosages using the Calvert formula. According to the median of calculated AUC, patients were divided into AUC ≥4 and <4 groups. Results: The median of AUC was 4 (1.8–5.5). A total of 79 patients had an AUC ≥4 and 72 patients had an AUC <4. The mean relative dose intensities of pemetrexed were 100.4% for the AUC ≥4 group, and 101.4% for <4 group. Baseline characteristic variables were balanced between the two groups, except for Eastern Cooperative Oncology Group Performance score ( P  = 0.044). The overall response rate (ORR) and disease control rate (DCR) were 33.8% and 90.1%, respectively, 35.4% and 86.1% for the AUC ≥4 group, and 31.9% and 94.4% for the AUC <4 group. No significant difference was observed in ORR ( P  = 0.650) and DCR ( P  = 0.086) between the two groups. Conclusion: Compared with an AUC of 5 or 6, the actual clinical application of AUC was generally insufficient for Chinese populations; fortunately, therapeutic efficacy remained equal. We found that AUC <4 was as adequate as AUC ≥4 in pemetrexed plus carboplatin regimen as first‐line treatment for them.